(untitled) (Strathmore Law Journal, 2023)
Causation in insurance law refers to the cause-and-effect relationship between an event and the resulting loss or damage. Causation is an important concept because it determines whether an insured party is entitled to coverage under a particular policy. There are several legal principles that are used to evaluate causation in insurance disputes, including the proximate cause rule and the ‘but for’ test. The ‘but for’ test, which inquires whether the loss would not have occurred ‘but for’ the occurrence of the covered event, has been criticized for its oversimplification of the causation analysis and its failure to adequately consider the complex causal chain that often underlies loss. In addition, the ‘but for’ test tends to draw a number of false negatives while taking into account certain irrelevant considerations. In contrast, the proximate cause rule, which requires that the covered event be the primary cause of the loss or damage, offers a more nuanced and comprehensive approach to causation analysis. It considers the full range of factors that may have contributed to the loss or damage and allows for a more flexible and context-specific analysis of causation. This article argued that the ‘but for’ test is an unreliable method for proving causation in insurance law and that the proximate cause rule is more appropriate. This article concluded that the proximate cause rule is a more reliable method for proving causation in insurance law and should be adopted as the standard for determining coverage under an insurance policy.